(untitled) (Research, Society and Development, 2021)
The aim of this study was to investigate whether the permanence of cage-free eggs in the nests compromises their internal quality. 660 commercial Isa Brown laying eggs, 31 weeks old, were distributed in two independent studies. In study 1, the quality of 180 fresh eggs submitted to different permanence times in the nest (0h, 2h, 4h, 6h) was evaluated. Egg weight, albumen height, Haugh Unit and Yolk Index were analyzed. In study 2, 480 eggs were stored in a 4 x 5 factorial scheme [length of permanence in the nest (0h, 2h, 4h, 6h) vs storage period (0, 7, 14, 21 and 28 days)]. Albumen height, Haugh Unit, Yolk Index, yolk and albumen pH, lipid oxidation and egg weight loss were evaluated. Significant changes were observed for Haugh Unit and albumen height in fresh eggs, as the eggs remained in the nest, with lower values (P<0.05) 6 h post-laying. In stored eggs, there was significant interaction between the permanence time in the nest and the storage period for Haugh Unit, albumen height, yolk pH and lipid oxidation. During storage there was loss of quality, with lower (P<0.05) Yolk Index and greater (P<0.05) weight loss at 28 days. The albumen pH was higher (P<0.05) from the 7th to the 28th day of storage. It is concluded, therefore, that cage-free eggs must be collected as soon as possible, preferably up to 4 hours after laying, once their losses in quality are constant throughout their permanence in the nest, being reflected during the storage of the eggs.